Strategi Guru Dalam Mengatasi Keterbatasan Media Pembelajaran Anak Usia Dini di Paud Nyiur Hijau Suwawa Selatan - Zahwa Fitria Yusuf; Ravika Latedu; Haryanti Huna; Miranti Labdulah; Indri Handayani Dulusea (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study was conducted to determine teachers’ strategies in overcoming the limitations of learning media for early childhood education at PAUD Nyiur Hijau Suwawa Selatan and to identify the relationship between teachers’ strategies and the effectiveness of early childhood learning. The research was carried out directly at the research location using data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of the principal and teachers at PAUD Nyiur Hijau Suwawa Selatan. The results showed that teachers’ strategies in overcoming the limitations of learning media were in the fairly good category with a percentage of 60.0%. Meanwhile, the effectiveness of early childhood learning was in the fairly effective category with a percentage of 57.5%. The correlation analysis using the Pearson Product Moment formula obtained a value of 0.53, indicating a positive relationship with a moderate level between teachers’ strategies in overcoming the limitations of learning media and the effectiveness of early childhood learning. Based on these findings, it can be concluded that teachers’ strategies play an important role in supporting the early childhood learning process. Teachers were able to utilize simple media such as natural materials, used goods, and the surrounding environment as alternative learning media so that the learning process could continue effectively even though the available learning media were limited.